Exploring The Metaverse: A Comprehensive Bibliometric Review Using Scopus Database - Pooja Sehgal Tabeck; Vinamra Jain (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Metaverse is fast growing and emerging technology domain which has been adopted all around the world by organizations in different facets of business. The penetration of the internet and social media all around the world has paced the adoption where Gaming and social media companies are torch-bearers of the metaverse. As the metaverse becomes popular among various domains which include education, health, marketing, fashion, finance, and many more, the field of research has also seen the adoption of metaverse as a field of study by academicians around the world. Despite the growing domain of research, there is a dearth of review studies in the field of the metaverse, to fill the void authors conducted a bibliometric analysis. The Scopus database is taken into consideration to perform bibliometric analysis using the Vosviewer tool. The study identified the top publication and growth trends, domains, geographical distribution of documents and keyword analysis. Key results depict that as metaverse is related to technological advancements, the maximum research has also been done in the field of computer science and engineering. The contribution in the field from technologically advanced countries is highest, whereas from less developed countries the contribution in the field is negligible.